Evaluation of Renal Protection From High Doses of Melatonin in an Experimental Model of Renal Ischemia and Reperfusion in Hyperglycemic Rats - Souza, A. V. G. de [UNESP]; Golim, Marjorie de Assis [UNESP]; Deffune, Elenice [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Carvalho, L. R. de [UNESP]; Vianna, I. G. [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP] (Elsevier B.V., 2014)
Background. Melatonin is a free radical scavenger with important actions in the study of renal ischemia and reperfusion (I/R). This study evaluated possible renal protection of high doses of melatonin in an experimental model of I/R in which rats were submitted to acute hyperglycemia under anesthesia with isoflurane.Method. Forty-four male Wistar rats, weighing more than 300 g, were randomly divided into 5 groups: G1, sham (n = 10); G2, melatonin (n = 10; 50 mg.kg(-1)); G3, hyperglycemia (n = 9; glucose 2.5 g.kg(-1)); G4, hyperglycemia/melatonin (n = 10; 2.5 g.kg(-1) glucose + melatonin 50 mg.kg(-1)); and G5, I/R (n = 5). In all groups, anesthesia was induced with 4% isoflurane and maintained with 1.5% to 2.0% isoflurane. Intraperitoneal injection of melatonin (G1, G4), glucose (G3, G4), or saline (G1, G5) was performed 40 minutes before left renal ischemia. Serum plasma values for creatinine and glucose were determined at baseline (M1), immediately following reperfusion (M2), and 24 hours after completion of the experiment (M3). Histological analysis was performed to evaluate tubular necrosis (0-5).Results. Serum glucose was higher at M2 in the groups supplemented with glucose, hyperglycemia (356.00 +/- 107.83), and hyperglycemia/melatonin (445.3 +/- 148.32). Creatinine values were higher at T3 (P = .0001) for I/R (3.6 +/- 0.37), hyperglycemia/melatonin (3.9 +/- 0.46), and hyperglycemia (3.71 +/- 0.69) and lower in the sham (0.79 +/- 0.16) and melatonin (2.01 +/- 1.01) groups, P < .05. Histology showed no necrosis injury in the G1, lesion grade 2 in the G2, and severe acute tubular necrosis in the G3: (grade 4), G4: (grade 5) and G5: (grade 4) groups (P < .0001).Discussion. Melatonin protected the kidneys submitted to I/R in rats without hyperglycemia; however, this did not occur when the I/R lesion was associated with hyperglycemia.Conclusions. Due to its antioxidant and antiapoptotic action, melatonin was able to mitigate, but not prevent acute tubular necrosis in rats with hyperglycemia under anesthesia by isoflurane.